TUNING ELECTRONIC AND MAGNETIC PROPERTIES OF CUBIC SRRUO3 SYSTEMS USING IN-PLANE STRAIN AND DEFECT VARIATIONS: A FIRST-PRINCIPLE STUDY - Dwi Wulandari, Retno
For the past few decades, strongly correlated materials have attracted much attention because they exhibit interesting and unique physical properties which not found in conventional metals and semiconductors. One of the fascinating systems is transition metal oxides (TMOs), where electrons in unoccupied d orbitals in a transition metal ion play an important role in physical properties. In addition, strong hybridization between these orbitals generates relatively wide d bands, being favorable for metallic conduction. Using a first-principle calculation method, the structural, electronic, and magnetic properties of cubic SrRuO3 unit cell in Pm3m space groups are calculated. The properties are modified by additional cadoping, forming Sr1-xCaxRuO3 with x = 0.25, 0.5, and 1 to SrRuO3 supercell system (2 x 2 x 1). In addition, oxygen-vacancies and ruthenium vacancies were applied in the system, forming SrRuO3-x and SrRu1-xO3 with x = 0.25 and 0.5, respectively. The main goals of this research are to model the properties of the systems by revealing magnetic moment values, the total density of states (DOS), and projected DOS (PDOS). The method used is generalized gradient approximation (GGA) corrected and correction of Hubbard U and exchange energies J, which are validated by calculating properties of pure SrRuO3 . Effective on-site Coulomb repulsion energy (Ueff) is included at d orbital to correct electronic properties. The structural properties of pure SrRuO3 unit cell system were fully optimized using the ‘vc-relax’ calculation with the initial lattice parameters of a = 3.9557 Å from the previous (experimental) report. The full structural optimization employed threshold force of 1 mRy/Bohr (~0.03 eV/Å). Employing ultrasoft pseudopotential, the values of U = 3.5 and J = 0.6 eV (Ueff = 2.9 eV) are the best choice for Pm3m space group. Then, we applied an x-axis strain (?xx) in a range ?xx????0.2 to ?2.0% on the system and optimize the atomic positions using the ‘relax’ calculation within the GGA + U method. We found the value of both in-plane and out-of-plane lattice parameter a is increase as the strain become larger, and so do for a total magnetic moment ? of the system. By additional ca-doping treatments, Sr1-xCaxRuO3 (x = 0.25, 0.5, and 1) system, we found that calcium atom alters crystal structure of the system due to the fact that radii of calcium are smaller than strontium atoms. However, the increment ca-doping only slightly enhances the magnetic moment. The differences only about 0.025 ?B between the pure SrRuO3 and Ca-doped SrRuO3. We also found in PDOS graphic that there is a weak Jahn-Teller distortion in eg states for both systems. Besides, the influence of oxygenvacancies is more obvious in the magnetic properties of the system. The total magnetic moment of the system becomes gradually suppressed due to the oxygen vacancies. For SrRuO3, the total magnetic moment is 2.3750 ?B and it becomes lower to 2.2750 ?B and 2.2000 ?B for SrRuO2.75 and SrRuO2.5, respectively. Jahn-Teller distortion is found more pronounce in these systems. It is found that in the t2g degeneration, there is a splitting in dxy and dzx/dzy levels where dxy have slightly higher energy than dzx and dzy. In addition, although Ru 4d states become reduced, ruthenium-vacancies increases the total magnetic moment of the system. This correspond to the O 2p states in near Fermi level and covalence band become pronounced. These SrRu1-xO3 systems also experienced strong Jahn-Teller distortion as seen in their PDOS graphic. For all the systems, it was found that Ru 4d orbital, hybridized with O 2p orbital, is the main contributor to ferromagnetic metallic properties. Ferromagnetic metallic properties, Jahn-Teller distortion (except pure SrRuO3), and reasonable lattice parameters have been obtained. This study allows us to predict the role of thin film strain on the structural, electronic and magnetic properties of SrRuO3 systems. These results are essential for novel functional device applications.